Language of tomorrow : towards a transcultural visual communication system in a posthuman condition - Nawar, Haytham (Intellect Books, 2020)
A comprehensive guide to the history, evolution and current forms of pictographic communication, from Mesopotamian writing systems to emojis. It also discusses the future of communication and the possibility of developing a standardized universal pictographic language. 73 b/w 37 col. illus.